Chemical composition, ruminal fermentation and greenhouse gases of diets with different levels of poultry manure - Ramírez , Roselia; Pinto , René; Camilo , Adriana; Molina , Luis; Hernández , David (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
The use of poultry manure in tropical cattle farming is common and although many aspects of this resource have been studied, it is important to generate information on the effects of including it in comprehensive diets. The objective of this work was to know the chemical, fermentative, greenhouse gas (GHG) production and costs characteristics of diets that include poultry manure. Three diets (treatments) made with local ingredients (30, 15 and 0 % poultry manure) were evaluated. For each treatment, crude protein values ​​and ruminal degradation, ash, fiber fractions, fermentation kinetics and fractions, GHG production and cost per kilogram were estimated. The results, except costs, were analyzed using the GLM procedure. Protein and fiber values ​​were similar (P>0.05) in all treatments while ash was higher (P<0.05) in those containing manure. The values ​​of Vm, Fm and FT were similar (P>0.05) in all treatments. In relation to GHG, the highest methane values ​​occurred in T3 (P<0.05) and those diets that included poultry manure were up to 20 % more economical. The inclusion of poultry manure in diets achieves protein contributions to the rumen similar to those achieved with diets based on which this byproduct was not included, as well as a greater contribution of ash without affecting ruminal fermentation activity, but it does reduce methane production and diet costs.